New high resolution Random Telegraph Noise (RTN) characterization method for resistive RAM. (January 2016) - Maestro, M.; Diaz, J.; Crespo-Yepes, A.; Gonzalez, M.B.; Martin-Martinez, J.; Rodriguez, R.; Nafria, M.; Campabadal, F.; Aymerich, X.
Abstract: Random Telegraph Noise (RTN) is one of the main reliability problems of resistive switching-based memories. To understand the physics behind RTN, a complete and accurate RTN characterization is required. The standard equipment used to analyse RTN has a typical time resolution of ∼2 ms which prevents evaluating fast phenomena. In this work, a new RTN measurement procedure, which increases the measurement time resolution to 2 μs, is proposed. The experimental set-up, together with the recently proposed Weighted Time Lag (W-LT) method for the analysis of RTN signals, allows obtaining a more detailed and precise information about the RTN phenomenon.